Chemical weathering processes generating the raw material used in porcelain stoneware industry in the São Paulo State, Brazil. (October 2022) - Meneghel, Eduardo Camargo; Tomazini da Conceição, Fabiano; Beltran Navarro, Guillermo Rafael; Christofoletti, Sérgio Ricardo; Marciano Motta, José Francisco
Abstract: The Paraná Sedimentary Basin (PSB) is an intracratonic basin located in the South America and some litostratigraphic units can be exploitable for different segments of non-metallic's industry. Brazil is one of the main producers in ceramic tiles market, specifically in the Santa Gertrudes Ceramic Pole (SGCP), São Paulo State. The Tatuí Formation is an Eopermian post-glacial marine unit from the PSB composed essentially of massive or laminated siltstones and pelites, interbedded with limestones and sandstones. These lithotypes are exploited and used as raw material to enhance the strength to porcelain stoneware industry in the São Paulo State, a product with greater added value in relation to the common "dry route" ceramic tiles produced in the SGCP. In order to understand the influence of the chemical weathering processes to generate the raw material used in the porcelain stoneware, we studied the mineralogy and geochemical characteristics of the weathered samples at two mines located in the city of Tatuí and compared the results with fresh rock collected nearby. The fresh rocks are composed of quartz, albite, microcline and muscovite. The weathered samples from the top of the weathering profiles are composed of kaolinite, illite, quartz, iron hydroxides and rare microcline, while the bottom horizons are richer in montmorillonite and feldspar. From the bottom to top layers, geochemical results indicate progressively enrichment of Al2 O3, Fe2 O3 and TiO2 and depletion of the other major oxides, trace elements (except for Ni, Th and U) and REE. The Chemical Index of Alteration ( CIA ) and Chemical Index of Weathering ( CIW ) values increased from the bottom to the top in the isalteritic saprolite. The weathering trends indicated the partial hydrolysis as the main chemical weathering process at both study areas. The chemical weathering reactions generated an added value ceramic product higher than the traditional clay materials exploited at SGCP due to the presence of montmorillonite and the low content of Fe2 O3 . Highlights: Weathering processes generating the raw material used in porcelain stoneware industry were studied. There is an enrichment of Al2 O3, Fe2 O3 and TiO2 in the isalteritic saprolite. The weathering trends indicated the monossialitization as the main chemical weathering. The chemical weathering reactions generated an added value ceramic product.